Providing regular and frequent maps of losses and gains of farmland birds based on European monitoring data - Sergi Herrando; Guillem Pocull; Sara Fraixedas; Anna Gamero; David Martí; Oriol Solà; Dani Villero; Verena Keller; Petr Voříšek; Alena Klvaňová; Gabriel Gargallo; Vitalie Ajder; et al. (Conservation Biology, 2026)
Knowledge of species distributions is essential for informing policies on nature conservation and restoration. However, updating them on a regular basis and doing so in a harmonized manner at the international level is difficult. The European Bird Census Council integrated national monitoring data covering 5 years to update farmland bird distributions and assessed how they changed. We used these data on 50 farmland bird species to generate 10×10 km maps showing their probability of occurrence from 2018 to 2022. We produced these maps with weighted ensemble species distribution models. We also developed models for the previous 5 years and plotted the differences in probabilities of occurrence per 10 × 10‐km area between the two periods as calibrated change maps. We evaluated model performance at continental and regional levels and interpreted changes in probability of occurrence in relation to known abundance trends. Models showed good predictive performance (mean AUC ≈ 0.84; mean squared error ≈ 0.13). Change estimates were reliable for 43 species (high accuracy, low bias), and distribution changes were positively correlated with independent abundance trends (Pearson's r ≈ 0.50). Thus, the distribution maps for the two periods accurately captured species’ distribution patterns and their temporal changes for all species at the European scale and for the majority of species in all regions except southeastern Europe. Among the 43 species with reliable estimates, predicted occurrences declined for 33 species, increased for nine, and were the same for one species. For most species, the direction of change in distribution was consistent with changes in species overall abundance in the same period, except for four species. Overall, our results indicated a recent contraction of farmland bird distributions in Europe, highlighting the strong capacity of existing bird monitoring networks to provide continent‐wide species maps that can be updated regularly.

Continental‐wide prioritization of protected areas to address global and habitat‐specific goals for avian biodiversity conservation - Yanjie Xu; Diego Pavón‐Jordán; Tyler Hallman; Tristan R. M. Bakx; Lluís Brotons; Sergi Herrando; Alison Johnston; Brett K. Sandercock; Thomas Sattler; Alaaeldin Soultan; Vitalie Ajder; Dawn E. Balmer; et al. (Conservation Biology, 2026)
The United Nations and European Union have set ambitious conservation goals to halt and reverse declines in biodiversity by protecting 30% of land and sea areas by 2030. Effective conservation planning requires evidence‐based spatial prioritization to maximize the coverage of species within designated protected areas. Based on a pan‐European database for occurrence and abundance of breeding birds collected in the 2010s, we applied the Zonation algorithm to identify key areas that would maximize the protection of ranges and populations for 435 species of breeding birds across Europe using either continental or national prioritization targets. When 30% of Europe's highest priority terrestrial areas were selected by the algorithm, 49% of species’ ranges and 63% of species’ populations were protected. When 10% and 30% of the highest priority lands were selected, compared with prioritization using occurrence data, prioritization using abundance data resulted in a higher percentage of species’ populations, especially rare and range‐restricted species, being represented for protected area coverage. Stratifying prioritization by habitat criteria greatly enhanced habitat‐specific conservation efficiency, enabling coverage of over 80% of breeding bird species’ populations in tundra, Mediterranean, and coastal habitats with a selection of 10% of the highest priority areas for each. Our prioritization supports international targets adopted under the Kunming–Montreal Global Biodiversity Framework by identifying key areas and providing a roadmap to guide optimal site protection and conservation planning in Europe.

Managed Aquifer Recharge: Modeling approaches to integrated assessment of groundwater interventions - Mina Yazdani; Peter van Thienen; Sija F. Stofberg; Marjolein H.J. van Huijgevoort; Ruud P. Bartholomeus (Groundwater for Sustainable Development, 2026)

Taraxacum koksaghyz Rodin as a versatile resource for the production of natural rubber and inulin - Jan-Peter Nap; Hetty C. van den Broeck; Jeroen van Arkel; Ruud A. de Maagd; Ingrid M. van der Meer (Biocatalysis and Agricultural Biotechnology, 2025)

Discovery of multiple bee-hazardous pesticides in ornamental plants via the Bee-Plex multi-target microsphere screening method - Rubing Zou; Ruud van Dam; Nathalie Smits; Erik Beij; Toine Bovee; Dirk C. de Graaf; Yirong Guo; Jeroen Peters (Journal of Hazardous Materials, 2025)

Visualisation and dissemination of 3D valuation units and groups – An LADM valuation information compliant prototype - Abdullah Kara; Peter van Oosterom; Ruud Kathmann; Christiaan Lemmen (Land Use Policy, 2023)

Community adaptation to temperature explains abrupt soil bacterial community shift along a geothermal gradient on Iceland - James T. Weedon; Erland Bååth; Ruud Rijkers; Stephanie Reischke; Bjarni D. Sigurdsson; Edda Oddsdottir; Jurgen van Hal; Rien Aerts; Ivan A. Janssens; Peter M. van Bodegom (Soil Biology and Biochemistry, 2023)

Safety of recycled plastics and textiles: Review on the detection, identification and safety assessment of contaminants - Anna K. Undas; Marc Groenen; Ruud J.B. Peters; Stefan P.J. van Leeuwen (Chemosphere, 2023)

Nano- and microplastics: a comprehensive review on their exposure routes, translocation, and fate in humans - Anja F.R.M. Ramsperger; Enrico Bergamaschi; Marco Panizzolo; Ivana Fenoglio; Francesco Barbero; Ruud Peters; Anna Undas; Sebastian Purker; Bernd Giese; Carina R. Lalyer; Alba Tamargo; M. Victoria Moreno-Arribas; et al. (NanoImpact, 2023)

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Tracking the Transport of Silver Nanoparticles in Soil: a Saturated Column Experiment - Karrar N. M. Mahdi; Ruud Peters; Martine van der Ploeg; Coen Ritsema; Violette Geissen (Water, Air, & Soil Pollution, 2018)

Consensus guidelines for the use and interpretation of angiogenesis assays - Patrycja Nowak-Sliwinska; Kari Alitalo; Elizabeth Allen; Andrey Anisimov; Alfred C. Aplin; Robert Auerbach; Hellmut G. Augustin; David O. Bates; Judy R. van Beijnum; R. Hugh F. Bender; Gabriele Bergers; Andreas Bikfalvi; et al. (Angiogenesis, 2018)

Effects of a cognitive dual task on variability and local dynamic stability in sustained repetitive arm movements using principal component analysis: a pilot study - Alessia Longo; Peter Federolf; Thomas Haid; Ruud Meulenbroek (Experimental Brain Research, 2018)

High-intensity interval training in hypoxia does not affect muscle HIF responses to acute hypoxia in humans - Stefan De Smet; Gommaar D’Hulst; Chiel Poffé; Ruud Van Thienen; Emanuele Berardi; Peter Hespel (European Journal of Applied Physiology, 2018)

Intrinsic factors influencing help-seeking behaviour in an acute stroke situation - Elles Zock; Henk Kerkhoff; Ruud Peter Kleyweg; Diederik van de Beek (Acta Neurologica Belgica, 2016)

Farmland biodiversity and agricultural management on 237 farms in 13 European and two African regions - Gisela Lüscher; Youssef Ammari; Aljona Andriets; Siyka Angelova; Michaela Arndorfer; Debra Bailey; Katalin Balázs; Marion Bogers; Robert G. H. Bunce; Jean‐Philippe Choisis; Peter Dennis; Mario Díaz; et al. (Ecology, 2016)
Farmland is a major land cover type in Europe and Africa and provides habitat for numerous species. The severe decline in farmland biodiversity of the last decades has been attributed to changes in farming practices, and organic and low‐input farming are assumed to mitigate detrimental effects of agricultural intensification on biodiversity. Since the farm enterprise is the primary unit of agricultural decision making, management‐related effects at the field scale need to be assessed at the farm level. Therefore, in this study, data were collected on habitat characteristics, vascular plant, earthworm, spider, and bee communities and on the corresponding agricultural management in 237 farms in 13 European and two African regions. In 15 environmental and agricultural homogeneous regions, 6–20 farms with the same farm type (e.g., arable crops, grassland, or specific permanent crops) were selected. If available, an equal number of organic and non‐organic farms were randomly selected. Alternatively, farms were sampled along a gradient of management intensity. For all selected farms, the entire farmed area was mapped, which resulted in total in the mapping of 11 338 units attributed to 194 standardized habitat types, provided together with additional descriptors. On each farm, one site per available habitat type was randomly selected for species diversity investigations. Species were sampled on 2115 sites and identified to the species level by expert taxonomists. Species lists and abundance estimates are provided for each site and sampling date (one date for plants and earthworms, three dates for spiders and bees). In addition, farmers provided information about their management practices in face‐to‐face interviews following a standardized questionnaire. Farm management indicators for each farm are available (e.g., nitrogen input, pesticide applications, or energy input). Analyses revealed a positive effect of unproductive areas and a negative effect of intensive management on biodiversity. Communities of the four taxonomic groups strongly differed in their response to habitat characteristics, agricultural management, and regional circumstances. The data has potential for further insights into interactions of farmland biodiversity and agricultural management at site, farm, and regional scale.

Continent‐scale global change attribution in European birds ‐ combining annual and decadal time scales - Peter Søgaard Jørgensen; Katrin Böhning‐Gaese; Kasper Thorup; Anders P. Tøttrup; Przemysław Chylarecki; Frédéric Jiguet; Aleksi Lehikoinen; David G. Noble; Jiri Reif; Hans Schmid; Chris van Turnhout; Ian J. Burfield; et al. (Global Change Biology, 2016)
Species attributes are commonly used to infer impacts of environmental change on multiyear species trends, e.g. decadal changes in population size. However, by themselves attributes are of limited value in global change attribution since they do not measure the changing environment. A broader foundation for attributing species responses to global change may be achieved by complementing an attributes‐based approach by one estimating the relationship between repeated measures of organismal and environmental changes over short time scales. To assess the benefit of this multiscale perspective, we investigate the recent impact of multiple environmental changes on European farmland birds, here focusing on climate change and land use change. We analyze more than 800 time series from 18 countries spanning the past two decades. Analysis of long‐term population growth rates documents simultaneous responses that can be attributed to both climate change and land‐use change, including long‐term increases in populations of hot‐dwelling species and declines in long‐distance migrants and farmland specialists. In contrast, analysis of annual growth rates yield novel insights into the potential mechanisms driving long‐term climate induced change. In particular, we find that birds are affected by winter, spring, and summer conditions depending on the distinct breeding phenology that corresponds to their migratory strategy. Birds in general benefit from higher temperatures or higher primary productivity early on or in the peak of the breeding season with the largest effect sizes observed in cooler parts of species' climatic ranges. Our results document the potential of combining time scales and integrating both species attributes and environmental variables for global change attribution. We suggest such an approach will be of general use when high‐resolution time series are available in large‐scale biodiversity surveys.

Progress and future of in vitro models to study translocation of nanoparticles - Hedwig M. Braakhuis; Samantha K. Kloet; Sanja Kezic; Frieke Kuper; Margriet V. D. Z. Park; Susann Bellmann; Meike van der Zande; Séverine Le Gac; Petra Krystek; Ruud J. B. Peters; Ivonne M. C. M. Rietjens; Hans Bouwmeester (Archives of Toxicology, 2015)

A review of the proximate composition and nutritional value of Marula (Sclerocarya birrea subsp. caffra) - Penny Hiwilepo-van Hal; Peter George Bille; Ruud Verkerk; Martinus A. J. S. van Boekel; Matthijs Dekker (Phytochemistry Reviews, 2014)

TGF-ß induces Lysyl hydroxylase 2b in human synovial osteoarthritic fibroblasts through ALK5 signaling - Dennis F. G. Remst; Esmeralda N. Blaney Davidson; Elly L. Vitters; Ruud A. Bank; Wim B. van den Berg; Peter M. van der Kraan (Cell and Tissue Research, 2014)

Leaf habit and woodiness regulate different leaf economy traits at a given nutrient supply - Jenny C. Ordoñez; Peter M. van Bodegom; Jan-Philip M. Witte; Ruud P. Bartholomeus; Han F. van Dobben; Rien Aerts (Ecology, 2010)
The large variation in the relationships between environmental factors and plant traits observed in natural communities exemplifies the alternative solutions that plants have developed in response to the same environmental limitations. Qualitative attributes, such as growth form, woodiness, and leaf habit can be used to approximate these alternative solutions. Here, we quantified the extent to which these attributes affect leaf trait values at a given resource supply level, using measured plant traits from 105 different species (254 observations) distributed across 50 sites in mesic to wet plant communities in The Netherlands. For each site, soil total N, soil total P, and water supply estimates were obtained by field measurements and modeling. Effects of growth forms, woodiness, and leaf habit on relations between leaf traits (SLA, specific leaf area; LNC, leaf nitrogen concentration; and LPC, leaf phosphorus concentration) vs. nutrient and water supply were quantified using maximum‐likelihood methods and Bonferroni post hoc tests. The qualitative attributes explained 8–23% of the variance within sites in leaf traits vs. soil fertility relationships, and therefore they can potentially be used to make better predictions of global patterns of leaf traits in relation to nutrient supply. However, at a given soil fertility, the strength of the effect of each qualitative attribute was not the same for all leaf traits. These differences may imply a differential regulation of the leaf economy traits at a given nutrient supply, in which SLA and LPC seem to be regulated in accordance to changes in plant size and architecture while LNC seems to be primarily regulated at the leaf level by factors related to leaf longevity.

A comparison of faecal analysis with backtracking to determine the diet composition and species preference of the black rhinoceros (Diceros bicornis minor) - Ruud J. van Lieverloo; Bjorn F. Schuiling; Willem F. de Boer; Peter C. Lent; Christine B. de Jong; Derek Brown; Herbert H. T. Prins (European Journal of Wildlife Research, 2009)

Characterisation of the Aspergillus niger dapB gene, which encodes a novel fungal type IV dipeptidyl aminopeptidase - Ruud Jalving; Jeroen Godefrooij; Wim J. ter Veen; Albert J. J. van Ooyen; Peter J. Schaap (Molecular Genetics and Genomics, 2005)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Benign recurrent intrahepatic cholestasis (BRIC): evidence of genetic heterogeneity and delimitation of the BRIC locus to a 7-cM interval between D18S69 and D18S64 - Richard J. Sinke; Victoria E. H. Carlton; Jenneke A. Juijn; Tammo Delhaas; Gerard P. Berge Henegouwen; Jan van Hattum; Klaus M. Keller; Maarten Sinaasappel; Charles M. A. Bijleveld; Hans-Kristian Ploos van Amstel; Peter L. Pearson; Nelson B. Freimer; et al. (Human Genetics, 1997)